2021
DOI: 10.1002/jgt.22670
|View full text |Cite
|
Sign up to set email alerts
|

A short note on conflict‐free coloring on closed neighborhoods of bounded degree graphs

Abstract: The closed neighborhood conflict-free chromatic number of a graph G, denoted by χ G ( )

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Note that this result gives a logarithmic (in normalΔ) lower bound on the conflict‐free chromatic number for a specific family of graphs, unlike other lower bounds mentioned, based on probabilistic constructions. We remark that an open neighborhood analog of the following theorem has been proved in an independent work by Bhyravarapu, Kalyanasundaram, and Mathew [3].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Note that this result gives a logarithmic (in normalΔ) lower bound on the conflict‐free chromatic number for a specific family of graphs, unlike other lower bounds mentioned, based on probabilistic constructions. We remark that an open neighborhood analog of the following theorem has been proved in an independent work by Bhyravarapu, Kalyanasundaram, and Mathew [3].…”
Section: Introductionmentioning
confidence: 84%
“…In 2009 Pach and Tardos showed that the answer is of order at most ln2+ϵ normalΔ and at least ln normalΔ [10]. Both bounds have been improved to normalΘ(ln2 Δ); Glebov, Szabó, and Tardos showed that certain random graphs on n vertices require at least normalΩ(ln2 n) colors [5], while Bhyravarapu, Kalyanasundaram, and Mathew gave a randomized procedure that constructs conflict‐free colorings using O(ln2 Δ) colors [2]. Constants hidden in the normalΩ,O‐notations are different, as one might expect from probabilistic proofs, but if we focus only on the order of magnitude—the question is completely answered and the mentioned results can be thought of as a conflict‐free analog of Brooks’ theorem.…”
Section: Introductionmentioning
confidence: 99%